Controls of aeolian and fluvial sediment influx to the northern Red Sea over the last 220 000 years - W. Ehrmann; P. A. Wilson; H. W. Arz; G. Schmiedl (Climate of the Past)
Present-day sediment influx to the northern Red Sea is dominated by aeolian dust because of its position between the large deserts of northern Africa, the Arabian Peninsula, and the Levant, as well as the absence of discharge from perennial rivers. However, sediment cores retrieved from the northern Red Sea reveal strong temporal variability in dust influx to the basin on glacial–interglacial timescales and several shorter-term strong episodes of fluvial input. We report new palaeoclimate and sediment provenance records for the last ca. 220 kyr from marine sediment core KL23, retrieved from the northern part of this basin. Our data suggest that the Nile delta became a major dust source during glacial conditions, in response to the glacioeustatic sea-level fall and associated subaerial exposure of volcanic-rich debris originally transported down the River Nile from the Ethiopian Highlands. Windblown dust from this delta source is characterized by high smectite concentrations and Ti contents. It is transported to the northern Red Sea on prevailing NNW winds. Our data also suggest a contribution of kaolinite-rich windblown dust from Egypt, Sinai, and the Levant to KL23 on the same winds. The activity of this source is hydrologically controlled, with minima in kaolinite concentrations documenting phases of increased humidity, probably due to enhanced Mediterranean cyclogenesis and a southward expansion of the Mediterranean winter rains. Short-term reactivations of wadi systems during fluvial episodes are identified by maxima in the abundance of clay-sized terrigenous sediment components, high chlorite concentrations, and high εNd. These episodes correlate with phases of reduced aeolian influx to the northern Red Sea and coincide with African humid periods, both in timing and relative intensity. This result implies that the Mediterranean climate system and the African monsoon are closely coupled.